Evaluation of Agro-Industrial by Products as Potential Local Feed for Ruminant Animals: Chemical Composition, Fiber Fractions and In Vitro Rumen Fermentation - Pratama, Said Mirza; Wajizah, Sitti; Jayanegara, Anuraga; Samadi, Samadi (ANIMAL PRODUCTION, 2018)
Animals are considered as source of protein should be improved their productivity with the minimum cost production. Agro-industrial by products have been used as animal feed to reduce feed cost. The purpose of this study is to evaluate agro-industrial by product in Aceh as potential local feed for ruminant animals based on chemical composition, fiber fraction and in vitro rumen fermentation. There were eight sources of agro-industrial by products (sago residues, coconut meal, soybean-ketchup by product, coffee pulp, cacao pod, sago tree, corncob, and rice brand) which were collected from 3 different locations in Aceh.  All agro-industrial by product samples were dried at 600C for 24 h and ground to pass a 1 mm sieve. Grounded samples were analyzed to determine chemical composition, fiber fractions and in vitro rumen fermentation. Incubation was conducted at temperature 390C for 48 h in water bath with three replicates. Data for in vitro rumen fermentation were statically calculated by using SPSS differences between treatments were stated (P≤0.05) by using Duncan Multiple Range Test (DMRT). The results indicated that agro industrial by product from coconut meal, ketchup residues, coffee by product, cacao by product, and rice brand can be used as source of protein and industrial by product from sago by product, sago tree and corncob can be used as source of energy. Neutral detergent  insoluble  CP (NDICP) and Acid detergent insoluble CP (ADICP)  were relatively high for sago by product, sago tree and rice brand but relatively low for cacao by product and corncob. The value of incubated pH for most feed samples was in the normal range. In vitro dry matter digestibility (IVDMD) and in vitro organic matter  digestibility (IVOMD) were significantly difference (P≤0.05) each agro-industrial by products with the highest for sago and the lowest for coffee by product. In conclusion, agro-industrial by products had a potential feed for ruminant animals both as protein and energy sources. However, feed ingredients with high fiber content and low degradability, further treatments such as physical, chemical and biological treatments were required to improve the feed quality.